2022
DOI: 10.7759/cureus.30509
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of CD44 and CD133 in Colorectal Stem Cell Cancer

Abstract: Colorectal cancer (CRC) is the most preventable malignancy globally, with a high mortality rate. Cancer stem cells (CSCs) are found previously in multiple types of cancer; CRC is one of them, and it has been correlated with several biomarkers. The two most essential markers related to colorectal CSCs are CD44 and CD133, which play a significant role in diagnosis, treatment, and prognosis. Unfortunately, the CSCs with positive CD44 and CD133 biomarkers illustrated an alarming prognosis. Several trials were tryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…We opted to focus on studying the metabolic pathways in A2780 and IGROV1, which are representative models for poorly differentiated OV with a high likelihood of relapse and consistently exhibit high genomic instability [20,21]. To con rm that the spheroids have the characteristics of CSCs functionally and morphologically, we assessed the expression of CD44 and CD133 proteins, which are stem cell markers that contribute to sphere formation and tumor cell biogenesis [22,23], using western blotting. CD44 was signi cantly more abundant in 3D-spheroids relative than in conventional 2D-cultured cells in IGROV1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We opted to focus on studying the metabolic pathways in A2780 and IGROV1, which are representative models for poorly differentiated OV with a high likelihood of relapse and consistently exhibit high genomic instability [20,21]. To con rm that the spheroids have the characteristics of CSCs functionally and morphologically, we assessed the expression of CD44 and CD133 proteins, which are stem cell markers that contribute to sphere formation and tumor cell biogenesis [22,23], using western blotting. CD44 was signi cantly more abundant in 3D-spheroids relative than in conventional 2D-cultured cells in IGROV1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In CRC, markers such as CD133, CD44, Oct-4, and Nanog are commonly used to identify and isolate cancer stem cells [ 49 , 50 ]. In addition, CD133, CD44, and Nanog may have clinical roles in predicting pathological stages, cancer recurrence, and therapy resistance in CRC [ 51 , 52 ]. In this study, the tumor sphere formation assay showed that the expression level of BAP31 was positively correlated with the cancer stemness of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…CSCs appear to be related to the resistance of cancer to therapy. 31 CD133 and CD44 are the most used markers for CSCs analysis in CRC, [32][33][34][35] been associated with cancer progression, 36 poor prognosis 37 and resistance to therapy. 38 Then, we investigated a possible enrichment of CSCs after single treatments or co-treatment (Figure 1H and Figure S3E,F).…”
Section: -Fu and Oxa Co-treatment Exert An Additive Cytotoxic Effect ...mentioning
confidence: 99%